Preventing of Technogenic Risks in the Functioning of an Industrial Enterprise - Kuzemin, A.; Mohammad, A.; Kots, G.; Lyashenko, V.; Tkachenko, M. (IAEME publication, 2016)
Providing safety of human life is inextricably linked to the study and analysis of the various emergency situations. At the same time a special place in this analysis is given to research the effect of the natural diseases on th ability of the possibility of occurrence and spread of the technogenic risk in the functioning of the industrial enterprise. To solve a problem The paper considers the basic principles of construction of distributed geographic information system for the management of technological risks in the functioning of industrial enterprise in case of natural emergencies. Disclosed some issues of functioning of specialized geoinformation systems preventing of technogenic risks in the functioning of an industrial enterprise.
Keywords: Information; Monitoring; Data Analysis